Psychological impact of the 2023 Kahramanmaraş earthquakes: a systematic review and meta-analysis of PTSD, depression, and anxiety among Turkish adults - Çınaroğlu, Metin; Yılmazer, Eda; Noyan Ahlatcıoğlu, Esra; Ülker, Selami Varol; Hızlı Sayar, Gökben (Frontiers in Public Health, 2025)
BackgroundThe twin earthquakes that struck Kahramanmaraş, Türkiye, on February 6, 2023, caused widespread devastation and loss of life. Beyond the physical destruction, such large-scale disasters often result in significant psychological trauma. This study systematically reviewed and meta-analyzed the prevalence and severity of probable post-traumatic stress disorder (PTSD), depression, and anxiety among adult Turkish survivors during the first 18 months post-disaster.MethodsFollowing PRISMA 2020 guidelines, a systematic search of Web of Science, PubMed, and Scopus was conducted for peer-reviewed studies published between February 6, 2023, and May 30, 2025. Eligible studies included quantitative assessments of PTSD, depression, or anxiety using validated Turkish-language scales, with general adult population samples (N ≥ 370). Eight studies (N = 5,965) met inclusion criteria. A random-effects meta-analysis was conducted for studies reporting prevalence of probable PTSD, while depression and anxiety outcomes were synthesized descriptively due to limited and heterogeneous data. Risk factors for psychological morbidity were also extracted and analyzed. This review was registered with PROSPERO (CRD42025644127).ResultsThe pooled prevalence of probable PTSD was 41% (95% CI: 32–52%). Reported PTSD rates ranged from 29 to 54%, and symptom severity remained high throughout the first year. Depression and anxiety were also widespread, with up to 40% screening positive for depression and 40–50% reporting moderate-to-severe anxiety symptoms. Comorbidity between PTSD, depression, and anxiety was common. Significant risk factors included female gender, bereavement, home destruction, displacement, job loss, and low social support. Resilience was protective in some studies, though findings were inconsistent.ConclusionEighteen months after the 2023 Kahramanmaraş earthquakes, Turkish adult survivors continued to experience high levels of probable PTSD, depression, and anxiety. These findings highlight a prolonged mental health crisis and underscore the urgent need for sustained, targeted psychosocial interventions. Integrating mental health support into disaster preparedness and long-term recovery efforts is essential for mitigating psychiatric morbidity in future disasters.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025644127.